2007
DOI: 10.1021/je600527c
|View full text |Cite
|
Sign up to set email alerts
|

Solubilities of Benzoic Acid and Phthalic Acid in Acetic Acid + Water Solvent Mixtures

Abstract: The solubilities of benzoic acid and phthalic acid in acetic acid + water solvent mixtures are determined by a static method. The experimental temperature ranges from (298.3 to 367.9) K, and the mass fraction of acetic acid in the solvent mixtures ranges from 0.8 to 1.0. The experimental results show that, within the temperature range of the measurements, the solubility of benzoic acid and phthalic acid in all the mixtures shows an increasing trend as the temperature increases. The solubility of benzoic acid d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
115
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(125 citation statements)
references
References 11 publications
9
115
1
Order By: Relevance
“…2. In the case of acetic acid, Wang et al [15] recently reported their measured solubility data, which is considerably lower than that from Liu et al [14], Ma and Xia [16] and Kendall [41]. The comparisons are shown in Fig.…”
Section: Solubility Datamentioning
confidence: 81%
See 2 more Smart Citations
“…2. In the case of acetic acid, Wang et al [15] recently reported their measured solubility data, which is considerably lower than that from Liu et al [14], Ma and Xia [16] and Kendall [41]. The comparisons are shown in Fig.…”
Section: Solubility Datamentioning
confidence: 81%
“…Solution crystallization is often used as the final purification step in its production. A lot of research has been conducted to understand the solubility of benzoic acid in different solvents such as water, alcohols, acids, alkanes, and aromatics, and some of the data can be found in several solubility data compilations [6][7][8] and journal articles [9][10][11][12][13][14][15][16]. In this work, the solubility of benzoic acid in four different categories of organic solvents of acetone, 2-propanol, acetic acid and cyclohexane was investigated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Wilson and the NRTL models, which have been successfully used to describe the (solid + liquid) equilibrium (SLE) [9][10][11][12][13][14], were employed to correlate the experimental results. The interaction parameters of the models were obtained.…”
Section: Introductionmentioning
confidence: 99%
“…20 The Nyvlt equation was used to correlate the experimental data. To understand the solubility behavior of TPP and TPPMnCl in ethanol + water solvent mixtures, the thermodynamic parameters including dissolution enthalpy, dissolution entropy, isobaric heat capacity, and Gibbs free energy were investigated in detail with the Clark−Glew equation.…”
mentioning
confidence: 99%